A Study on Vaccination Hesitancy Caused by Misinformation in Hong Kong - Leung, Chi Hong (International Journal of Publication and Social Studies, 2022)
COVID-19 vaccination prevents the disease from spreading in society and aids to control the pandemic. However, there is vaccination hesitancy in which people are reluctant to get vaccinated. This paper discusses the general problems of vaccination hesitancy throughout the world and the specific problems in the societal context of Hong Kong, including the reasons why anti-vaxxers and political objectors refuse vaccination. Because one major reason for vaccination hesitancy is the misinformation on the Internet, the aim of this study is to collect and analyze the misinformation posted in the popular online discussion forum in Hong Kong. The content analysis of 3,310 messages shows most people are concerned about the safety and side effects of vaccines. Moreover, insufficient confidence in the vaccine manufacturers and confusing information influence the vaccination rate. Finally, the paper suggests a way to addressing vaccination hesitancy through sharing clear and accurate information to correct the improper one.